A phase II trial of valproic acid in patients with advanced, radioiodine‐resistant thyroid cancers of follicular cell origin. (8th September 2016) - Nilubol, Naris; Merkel, Roxanne; Yang, Lily; Patel, Dhaval; Reynolds, James C.; Sadowski, Samira M.; Neychev, Vladimir; Kebebew, Electron
Summary: Objective: Valproic acid (VA) is a histone deacetylase (HDAC) inhibitor that has antiproliferative effects on several types of cancer, including thyroid cancer. In addition, VA has been reported to upregulate the sodium‐iodine symporter in thyroid cancer cells and increases radioiodine uptake in preclinical studies. The aim of this study was to assess the antiproliferative effects of VA and to evaluate if VA can increase the radioiodine uptake in patients with advanced, radioiodine‐negative thyroid cancer. Design: An open‐label Simon two‐stage phase II trial. Patients and Measurements: Valproic acid was administered orally, and doses were adjusted to maintain serum trough levels between 50 and 100 mg/l for 10 weeks, followed by injections of recombinant human thyroid‐stimulating hormone and a radioiodine uptake scan. Anatomical imaging studies were performed at week 16 to assess tumour response and radioiodine therapy in patients with increased radioiodine uptake. Results: Thirteen patients with a median age of 66 years (50–78 years) were enrolled and evaluated. Seven patients had papillary thyroid cancer (PTC), two had follicular variant PTC, two had follicular thyroid cancer, and two had Hürthle cell carcinoma. None of the 10 patients who completed the 10‐week treatment had increased radioiodine uptake at their tumour sites. Three patients were taken off the study prior to the 10‐week radioiodine uptake scan: one with grade‐3 hepatic toxicity, one with disease progression and one for noncompliance. Four of 13 patients had decreased stimulated serum thyroglobulin with VA treatment. None of the patients had complete or partial responses based on Response Evaluation Criteria in Solid Tumors (RECIST), and six patients had disease progression. Conclusions: Valproic acid does not increase radioiodine uptake and does not have anticancer activity in patients with advanced, radioiodine‐negative thyroid cancer of follicular cell origin.